2000
DOI: 10.1021/jf000467t
|View full text |Cite
|
Sign up to set email alerts
|

Microdetermination of Diosgenin from Fenugreek (Trigonella foenum-graecum) Seeds

Abstract: Sulfuric acid hydrolysis of steroidal glycosides of Amber fenugreek was studied by capillary gas chromatographic analysis of diosgenin [(25R)-spirost-5-en-3-ol] and isomeric spirostadiene artifacts from 100 mg samples of seed material. Following extraction with 80% ethanol, highest recoveries of diosgenin occurred when hydrolyses were conducted in sulfuric acid, prepared at 1 molar (M) concentration in water containing 60-80% 2-propanol. Compared to a previous method with aqueous hydrochloric acid, the selecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
68
0
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(72 citation statements)
references
References 17 publications
3
68
0
1
Order By: Relevance
“…19). It has been reported that when the diosgenin glycoside, dioscin, was orally administered to rats, diosgenin was very poorly absorbed (0.2%; ref.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…19). It has been reported that when the diosgenin glycoside, dioscin, was orally administered to rats, diosgenin was very poorly absorbed (0.2%; ref.…”
Section: Discussionmentioning
confidence: 99%
“…1) is an aglycone of the steroidal saponin, dioscin, which is present at relatively high concentrations in the tubers of wild yams (Dioscorea villosa Linn) and the seeds of fenugreek (Trigonella foenum graecum Linn; refs. 19,20). Diosgenin is used for the commercial synthesis of steroid products, such as cortisone, pregnenolone, and progesterone.…”
Section: Introductionmentioning
confidence: 99%
“…The crude products were determined using thin layer chromatography (TLC) with Merck Silica Gel 60F-2504 glass plates. The product was analyzed by 1 …”
Section: General Methods For Dg Preparationmentioning
confidence: 99%
“…and other plants such as Smilax bockii warb and Trigonella foenum graecum. [1,2] DG has exhibited biological effects in the treatment of various diseases such as hypercholesterolemia, climacteric syndromes including diabetic neuropathy and even cancer. [3][4][5][6] It has also been claimed to have an osteogenic property.…”
Section: Introductionmentioning
confidence: 99%
“…1,2) Several in vivo studies have shown that diosgenin is effective in treating various diseases such as hyperglycemia and hyperlipidemia and has been established as a starting material for the production of several steroidal hormones by the pharmaceutical industry. [3][4][5] Diosgenin has also been used in hormone replacement therapy for menopausal women.…”
mentioning
confidence: 99%